Use of Continuous EEG Monitoring and Short-Term Outcomes in Critically Ill Children - Bozarth, Xiuhua Liang; Ko, Pin-Yi; Bao, Hao; Abend, Nicholas S.; Watson, R Scott; Qu, Pingping; Dervan, Leslie A.; Morgan, Lindsey A.; Wainwright, Mark; McGuire, John K.; Novotny, Edward (Journal of Pediatric Intensive Care, 2022)
This study aimed to compare short-term outcomes at pediatric intensive care unit (PICU) discharge in critically ill children with and without continuous electroencephalography (cEEG) monitoring. We retrospectively compared 234 patients who underwent cEEG with 2294 patients without cEEG. Propensity score matching was used to compare patients with seizures and status epilepticus between cEEG and historical cohorts. The EEG cohort had higher in-hospital mortality, worse Pediatric Cerebral Performance Category (PCPC) scores, and greater PCPC decline at discharge. In patients with status epilepticus, the PCPC decline was higher in the cEEG cohort. PCPC decline at PICU discharge was associated with cEEG monitoring in patients with status epilepticus.
Keywords: EEG monitoring; outcomes; critically ill children